2002
DOI: 10.1248/bpb.25.1277
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cell Surface Phosphatidylserine and Sugar Chains during Apoptosis and Their Time-Dependent Role in Phagocytosis by Macrophages.

Abstract: Apoptosis, or programmed cell death, is a process crucial in organ development and homeostasis. Apoptotic cells are fragmented and form so-called apoptotic bodies that are engulfed and degraded by neighboring phagocytes. In order to engulf apoptotic cells, receptors on the phagocytes must recognize ligands expressed exclusively on apoptotic cells. Apoptosis induces several cellular changes, including membrane blebbing, condensation of chromatin along the nuclear membrane, and the generation of membrane-enclose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Changes in the glycomic profile of apoptotic cells have previously been studied by various groups, who have analyzed cells of different origin (Azuma et al, 2002;Hart et al, 2000;Rapoport and Pendu, 1999). In these previous studies, both an increase and a decrease of membrane-bound Sias have been reported, depending on the cell type under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the glycomic profile of apoptotic cells have previously been studied by various groups, who have analyzed cells of different origin (Azuma et al, 2002;Hart et al, 2000;Rapoport and Pendu, 1999). In these previous studies, both an increase and a decrease of membrane-bound Sias have been reported, depending on the cell type under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acids are ubiquitously expressed at the nonreducing ends of oligosaccharide chains and are important in various biological events. During apoptosis they can be enzymatically removed to expose asialoglycoconjugates, which are relevant in inducing phagocytosis [39][40][41].…”
Section: 'Eat Me' Signals On the Surface Of Apoptotic Cellsmentioning
confidence: 99%
“…In 2000, a lectin-based approach for detecting apoptotic cells in flow cytometry detected a changed pattern of glycoproteins of the plasma membrane during apoptosis using the FITC-labeled lectin Narcissus pseudonarcissus (NPn) [53]. In 2004, application of the same using a flow cytometric procedure showed that apoptosis is associated with a marked decrease in cell surface sialylation.…”
Section: Identification Of Apoptotic Cells By Lectinsmentioning
confidence: 99%